Dinamika Politik Lokal dalam Pemilihan Kepala Daerah Calon Tunggal Pada Pemilihan Tahun 2024 Di Kabupaten Ciamis - Puji Lestari; Erlan Suwarlan; Abdul Mutholib (Kampus Akademik Publiser, 2025)
This study aims to analyze the political dynamics in the 2024 regional head election (Pilkada) in Ciamis Regency, which featured a single candidate. The phenomenon of single-candidate elections has become increasingly common in Indonesia and raises concerns in the context of local democracy, such as weak political competition, elite domination, and limited choices for voters. This research employs a descriptive qualitative approach using elite theory as the analytical tool, particularly the framework proposed by Mufti (2019), which divides elites into three main dimensions: their position in the social structure, their roles in institutions or organizations, and their control over power resources. Data were collected through interviews, observation, and documentation involving various informants, including political party members, academics, community leaders, youth figures, and voters who chose the blank box. The findings reveal that the dominance of the incumbent pair, Herdiat-Yana, was backed by all political parties in Ciamis, resulting in the absence of challengers. Public responses varied, from acceptance to choosing the blank box as a form of protest. This phenomenon reflects the limitations of substantive democracy at the local level. The study recommends reforming the regional head candidacy system and strengthening political participation to foster healthy political competition in future elections.